Inoculation of maize with Azospirillum brasilense in the seed furrow - Morais, Tâmara; Brito, Césio; Brandão, Afonso; Rezende, Wender (Revista Ciência Agronômica, 2016)
Several studies addressing the inoculation of cereals with diazotrophic microorganisms can be found in the literature. However, in many experiments, investigators have overlooked the feasibility of applying these microorganisms to the furrow together with the seed, and the effect of bacterial concentration on phytostimulation. The aim of this work was to evaluate the effect of doses of an inoculant based on Azospirillum brasilense, applied to the seed furrow when planting maize, combined with different doses of nitrogen fertiliser. The experiment was carried out in the field, in soil of the cerrado region of Brazil. An experimental design of randomised blocks in bands was adopted, comprising nitrogen (40, 100, 200 and 300 kg ha-1) and doses of an A. brasilense-based liquid inoculant applied to the seed furrow (0, 100, 200, 300 and 400 mL ha-1). The dose of 200 mL ha-1 Azospirillum was noteworthy for grain production. This is the first report of the effective application of Azospirillum in the seed furrow when planting maize in the cerrado region of Brazil.